Stigmatization and VVF-HIV/AIDS among young adults females : a critical pastoral assessment of the role of the ECWA (Evangelical Church West Africa) - Abraham, Yisa Thomas (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.